Emergency quarters - Matias, Carlos (Children's author) (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2024)
Author Carlos Matias and Ezra Jack Keats Award-winning illustrator Gracey Zhang deliver a stunning picture book based on a finalist in the New York Times Metropolitan Diary "Best of the Year," about a young boy in the city who tries his best to avoid spending his precious quarters on tempting local treats in case of an "emergency." A poignant, cheeky tale perfect for fans of Matt de La Peña, Antwan Eady, and Jacqueline Woodson. Ernesto has waited his whoooole life to become a niño grande. A big boy. Now he's finally old enough to walk the six blocks to school without his parents. Every morning, his mom hands him a shiny new quarter and reminds him they're for emergencies. If Ernesto needs her, she's only a pay phone call away. But each day reveals a tempting new treat to enjoy with his friends: crisp packs of baseball cards, arcade games, hot tamales, and fresh juices! Ernesto has the coins jingling in his pocket, so how will he choose to spend them?